Determinants of Nurses’ Turnover Intention: A Systematic Literature Review - Madamang, Irfan; Hasanuddin; Abriani (Ammar Dharma Foundation, 2025)
Background: Nurses play a pivotal role in ensuring healthcare quality and patient safety. However, many healthcare systems worldwide are struggling with high levels of nurse turnover. Turnover intention, defined as the cognitive process leading to the decision to leave a job, has been identified as the most immediate antecedent of actual turnover behavior, which can negatively impact healthcare delivery and organizational stability.Objective: To explore and synthesize the current empirical literature on the determinants of turnover intention among nurses, with the goal of identifying key contributing factors and informing effective nurse retention strategies.Methods: A systematic literature review was conducted using five major academic databases PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar. The search targeted peer-reviewed articles published between 2014 and 2024, in English or Indonesian, which investigated turnover intention among nurses. After screening 53 retrieved articles, 27 met the inclusion criteria and were analyzed thematically.Results: Six major determinants of turnover intention among nurses were identified: (1) job satisfaction, (2) occupational stress and burnout, (3) workload and working conditions, (4) organizational and peer support, (5) leadership style, and (6) demographic or individual characteristics. These factors often interact dynamically, forming a complex psychosocial and organizational environment that shapes nurses’ intention to stay or leave.Conclusion: Turnover intention is a multifaceted phenomenon, and addressing it requires integrated strategies targeting structural, managerial, and personal dimensions. Healthcare organizations must focus on improving working conditions, promoting effective leadership, supporting emotional well-being, and recognizing demographic differences to mitigate nurse attrition.